O+ Escape During the Extreme Space Weather Event of 4–10 September 2017. Issue 9 (14th September 2018) - Schillings, Audrey; Nilsson, Hans; Slapak, Rikard; Wintoft, Peter; Yamauchi, Masatoshi; Wik, Magnus; Dandouras, Iannis; Carr, Chris M.
Abstract: We have investigated the consequences of extreme space weather on ion outflow from the polar ionosphere by analyzing the solar storm that occurred early September 2017, causing a severe geomagnetic storm. Several X‐flares and coronal mass ejections were observed between 4 and 10 September. The first shock—likely associated with a coronal mass ejection—hit the Earth late on 6 September, produced a storm sudden commencement, and began the initial phase of the storm. It was followed by a second shock, approximately 24 hr later, that initiated the main phase and simultaneously the Dst index dropped to Dst = −142 nT and Kp index reached Kp = 8. Using COmposition DIstribution Function data on board Cluster satellite 4, we estimated the ionospheric O + outflow before and after the second shock. We found an enhancement in the polar cap by a factor of 3 for an unusually high ionospheric O + outflow (mapped to an ionospheric reference altitude) of 10 13 m −2 s −1 . We suggest that this high ionospheric O + outflow is due to a preheating of the ionosphere by the multiple X‐flares. Finally, we briefly discuss the space weather consequences on the magnetosphere as a whole and the enhanced O + outflow in connection with enhanced satellite drag. Key Points: Multiple X‐flares and three CMEs occurred in 4‐10 September 2017, CMEs are the driver of the storm, whereas the X‐flares might have preheated the ionosphere The O + outflow in the polar cap and cusp is estimated to be 10 13 m ‐2 s ‐1 during the main phase of the geomagnetic storm The entire magnetosphere is affected by space weather event, and the O + enhancement in the cusp might be a good indicator for satellite drag fluctuations